Short communication: Microfungal diversity on leaves of Eusideroxylon zwageri, a threatened plant species in Sarawak, Northern Borneo - A. Lateef, Adebola; Muid, Sepiah; Mohamad H., Bolhassan; Mansor, Wan Zamir (MBI & UNS Solo, 2015)
Adebola AL, Sepiah M, Bolhassan MH, Wan Zamir M. 2015. Microfungal diversity on leaves of Eusideroxylon zwageri, a threatened plant species in Sarawak, Northern Borneo. Biodiversitas 16: 264-268. A survey of the microfungal communities on green leaves and leaf litters of an endangered plant species, Eusideroxylon zwageri Teijsm. & Binn. (belian) was carried out for the first time. A total of 200 leaf segments were plated on both water agar and malt extract agar. 74 fungal species were identified from both leaf types with more fungal taxa found on the green leaves, with a Shannon diversity index of 3.85 compared to that on litters, 2.63 and the similarity between the microfungal communities on both leaf types was low with a Bray-Curtis similarity index of 0.366. The most dominant species on both leaf types includes Aphanocladium areanarum, Trichoderma koningii, Nectria sp., Chalara pteridina, Hyphomycetes sp.3, hyaline Mycelia sterilia, Circinotrichum sp., Phoma sp., Acremonium macroclavatum, Chaetopsina sp., Physarum sp., Beltrania rhombica and Colletotrichum acutatum.